Combining hydraulic model, hydrogeomorphological observations and chemical analyses of surface waters to improve knowledge on karst flash floods genesis - F. Raynaud; V. Borrell-Estupina; S. Pistre; S. Van-Exter; N. Bourgeois; A. Dezetter; E. Servat (Proceedings of the International Association of Hydrological Sciences, 2015)
During a flood event over a karst watershed, the connections between surface and ground waters appear to be complex ones. The karst may attenuate surface floods by absorbing water or contribute to the surface flood by direct contribution of karst waters in the rivers (perennial and overflowing springs) and by diffuse resurgence along the hillslopes. If it is possible to monitor each known outlet of a karst system, the diffuse contribution is yet difficult to assess. Furthermore, all these connections vary over time according to several factors such as the water content of the soil and underground, the rainfall characteristics, the runoff pathways. Therefore, the contribution of each compartment is generally difficult to assess, and flood dynamics are not fully understood. To face these misunderstandings and difficulties, we analysed surface waters during six recent flood events in the Lirou watershed (a karst tributary of the Lez, in South of France). Because of the specific chemical signature of karst waters, chemical analyses can supply information about water pathways and flood dynamics. Then, we used the dilution law to combine chemical results, flow data and field observations to assess the dynamics of the karst component of the flood. To end, we discussed the surface or karst origin of the waters responsible for the apparent runoff coefficient rise during flash karst flood.